Novel Electrospun Zwitterionic Nanofibers for Point‐Of‐Care Nucleic Acid Isolation Strategies Under Mild Conditions - Alissa J. Wieberneit; Nongnoot Wongkaew; Antje J. Baeumner (Advanced Materials Interfaces)
Abstract Nucleic acid (NA) testing at the point‐of‐care requires efficient NA extraction followed by post‐NA amplification to achieve necessary detection sensitivity. Nanofibers (NFs) are demonstrated to be an ideal solid surface in an NA extraction process but necessitate harsh conditions that interfere with the subsequent NA amplification process. It is demonstrated that novel, pH tunable, zwitterionic NFs composed of uncharged nylon doped with the weakly basic, cationic polyallylamine hydrochloride and the weakly acidic anionic polycarboxylic acid to address the issue. Unlike the other cationic polymers investigated, e.g. polybrene and polyaniline, these polymers allow efficient NA extraction in Tris‐ethylenediamine tetra‐acetic acid buffer under mild conditions (pH 4.5 containing 0.1% Tween 20 for adsorption, and pH 10 with 50 mM NaCl for elution). Adsorption and elution yields over 95% and 70%, respectively, are achieved. It also discovered a correlation between material morphologies and the NA extraction suggests that the combination of polymer chemistries and nanofiber morphologies facilitates efficient NA extraction at low concentrations (ng range) within a short time period (<10 min). Considering the simple protocols and instrument‐free operation the as‐developed NFs are highly attractive for use in sample‐to‐answer NA testing in point‐of‐care settings.